2020
DOI: 10.1088/1742-6596/1440/1/012104
|View full text |Cite
|
Sign up to set email alerts
|

Student critical thinking skills and learning motivation in elementary students

Abstract: Critical thinking skills are 21st century life skills that are very necessary for life. The purpose of this study is to analyze the level of critical thinking skills of students, and how influential learning motivation is on students’ critical thinking skills. The research method used is mixed methods with explanatory sequential strategy. The sample of this study were students in grade V SD Jagalan. Data collection is done by the method of tests, interviews, observations, and documentation. The results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…Students do not have an intrinsic ability or capacity for critical thinking. Although some students are inherently interested, they require instruction to absorb knowledge in an analytical, methodical, and open-minded manner (Fajari et al, 2020). Someone who knows is not necessarily able to think critically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students do not have an intrinsic ability or capacity for critical thinking. Although some students are inherently interested, they require instruction to absorb knowledge in an analytical, methodical, and open-minded manner (Fajari et al, 2020). Someone who knows is not necessarily able to think critically.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of education of Indonesian employees has an impact on this finding, particularly in terms of critical and analytical thinking abilities. Because a worker naturally follows formal schooling before looking for a job, pupils' critical thinking abilities at school might reveal the employees' inadequate critical thinking skills (Fajari et al, 2020). Some educational researchers across the level in Indonesia also reported the pedagogical strategies have not been optimal to develop the student's critical thinking skills where teachers did empower students with those skills (Fitriani et al, 2019;Kristiyanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study involved 35 fifth-grade students. The data were collected based on tests, interviews, observations and documentation; there were both qualitative and quantitative practices (Fajari, 2020). Despite a number of similarities, the major difference between this study and our research is that it was conducted among elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…The level of academic motivation in this study was defined based on the pattern that we also used in our research – the students were asked to answer the set of questions related to their attitude towards learning (Paul and Elder, 2019). Based on the results of categorization, it was revealed that 20% of students have strong academic motivation, 46% – moderate and 34% – low (Fajari, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, learning in schools should be able to develop students' critical thinking skills. Some experts have claimed that several things influenced critical thinking skills: physical concentration, learning concentration, intellectual development, and learning motivation (Gul et al, 2014;Saeger, 2014;Fajari et al, 2020b). Hakim et al (2018) argued that students' initial knowledge would influence their critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%